The full metamorphosis of λ-fold designs into λ-fold 3-star systems
Let (X, B) be a λ-fold λ-design. If a triangle is removed from each block of B the resulting collection of 3-stars; 5, is a partial λ-fold 3-star system; (X, S). If the edges belonging to the deleted triangles can be arranged into a collection of 3-stars T